America in the world : the historiography of American foreign relations since 1941 - Hogan, Michael J. 1943- (Cambridge Univ. Press, 1995)
America in the World includes state-of-the-art essays and historiographical surveys of American foreign relations since 1941 by some of the country's leading diplomatic historians. The essays by Bruce Cumings, Michael Hunt, and Melvyn P. Leffler in Part One offer sweeping overviews of the major trends in the field of diplomatic history. Part Two features essays that survey the literature on U.S. relations with particular regions of the world or on the foreign policies of presidential administrations by Mark A. Stoler, Howard Jones, Randall Woods, J. Samuel Walker, Rosemary Foot, John Ferris, Diane B. Kunz, Mark T. Gilderhus, Douglas Little, Robert J. McMahon, Stephen G. Rabe, Burton I. Kaufman, Gary R. Hess and Robert D. Schulzinger. The result is the most comprehensive assessment of the literature on U.S. foreign policy to be published in nearly twenty years.